Student Satisfaction with Online Teaching and Assessment during Covid 19 - Nauman Ahmed Noor, Aneela Qaisar, Sanam Ayesha, Saadia Bano Lone, Maria Asmat (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the student’s satisfaction with online teaching and assessment during the Covid-19 pandemic. Methodology: This cross-sectional squestionnaire based study was performed across six Medical and Dental colleges of Lahore. A questionnaire consisting of thirty questions was distributed through google forms. A total of (N = 460) students responded, and the results were presented in percentage frequency. Result: The present study revealed that 46% of the students believed that e-learning tool is not adequatefor basic and clinical sciences.The learning outcomes (35.1%) and objectives (33.8%) were not achieved through e-learning. The majority of the students agreed thatproblem-based learning is an effective way of teaching (37.7%). Online lectures were difficult to understand (35.1%). The students were not satisfied (23.4%) with the online assessment.The technical issues affected the performance of the students. Practical implication: This sudy identified different challenges of online teaching.Online education is a valuable learning tool and the online learning approach has been successfully integrated worldwide with conventional teaching of the curriculum. In order to keep up with the contemporary methods and with the introduction of newer technology and tools it is imperative that our teaching should incorporate e-learning strategies and curricula designed to match it. The policymakers and universities should enable teachers and students with proper training and facilities in this age of technological advancement.. Conclusion: Our study revealed that students were not satisfied withonline teaching however, they were indecisive about online assessment methodology. The students believed that lack of infrastructure and inadequate learning tools affected their performance.. Keywords: E-learning, online assessment, COVID-19, e-learning, problem based learning, learning management system